Beej Raksha: Reframing Cure in the Sacred Domain. (3rd July 2021) - Barrow, Giles; Pandya, Anisha
Abstract: The authors offer a cross-cultural account of healing and cure that can be useful across all fields of application in transactional analysis. Specifically, ideas from an Indian perspective are presented in which the role of guru energy and witnessing are reframed with illustrations using case material. The authors introduce a third level of communication and a fifth rule of communication that account for a sacred quality in the exploration of healing and cure.